Kasus kromoblastomikosis yang awalnya diduga furunkel pada seorang perempuan - Roslina Horo; Ni Luh Putu Ratih Vibriyanti Karna; Ni Putu Ayu Riska Yunita Sari (Intisari Sains Medis, 2022)
Background: Chromoblastomycosis is a chronic profound fungal infection caused by dematiaceous from the surrounding environment. Trauma was the site of fungal implantation. The prevalence is mainly in agriculture workers. The clinical picture varies. Diagnosis is made when muriform cells are found. Early diagnosis is very important because it affects the prognosis. Case Description: A woman, 24 years old, Balinese, went to The Skin and Genital Polyclinic of Sanglah General Hospital with the main complaint of boils in the area below the left knee six months ago. It starts from red papules and then becomes a painless lump.  The lump breaks and contains yellowish pus. Patients have a history of gardening. Physical examination within normal limits. Dermatological status on left cruris, there are solitary erythema nodules, firm borders, round shape, a diameter of 2.5 cm, smooth and shiny surface, and fluctuations containing yellowish pus. From sabouraud dextrose agar culture (SDA) obtained the growth of Cladophialophora carrionii. The diagnosis was chromoblastomycosis. Patients were given a pulse dose of itraconazole 400 mg every 24 hours intraorally. There was a clinical improvement. Conclusion: There have been reported cases of chromoblastomycosis that were initially suspected to be furuncle in a 24-year-old woman. Diagnosis is made based on anamnesis, physical examination, and laboratory examination. Patients were given a pulse dose of itraconazole. There was a clinical improvement. The prognosis is dubius ad bonam. Extended observations still need to monitor the clinical and mycological healing, medication side effects and complications of the disease.   Latar belakang: Kromoblastomikosis adalah infeksi jamur profunda kronik yang disebabkan oleh dematiaceous yang berasal dari lingkungan sekitar. Penyakit ini biasanya diawali oleh trauma sebagai situs implantasi jamur. Prevalensi penyakit ini terutama pada individu yang bekerja di bidang agrikultural. Gambaran klinis kromoblastomikosis bervariasi. Penegakan diagnosis bila ditemukan sel muriform pada jaringan. Diagnosis dini pada lesi awal sangat penting karena mempengaruhi prognosis penyakit. Deskripsi kasus: Seorang perempuan, 24 tahun, suku Bali, berobat ke Poliklinik Kulit dan Kelamin RSUP Sanglah Denpasar dengan keluhan utama bisul pada area bawah lutut kiri sejak 6 bulan yang lalu. Awalnya berupa bintil kemerahan lalu menjadi benjolan yang tidak nyeri. Benjolan pecah dan mengeluarkan nanah. Pasien memiliki hobi berkebun. Pemeriksaan fisik dalam batas normal. Status dermatologi pada regio kruris sinistra terdapat nodul eritema soliter, batas tegas, bentuk bulat, diameter 2,5 cm, permukaan halus dan mengkilap, tampak fluktuasi berupa pus kekuningan. Pemeriksaan kultur sabouraud dextrose agar (SDA) didapatkan pertumbuhan Cladophialophora carrionii. Diagnosis kerja adalah kromoblastomikosis. Pasien diterapi dengan itrakonazol 400 mg setiap 24 jam intraoral dosis denyut dan terdapat perbaikan klinis pada lesi.   Simpulan: Telah dilaporkan kasus kromoblastomikosis yang awalnya diduga furunkel pada seorang perempuan usia 24 tahun. Diagnosis ditegakkan berdasarkan anamnesis, pemeriksaan fisik, dan pemeriksaan penunjang. Pasien diberikan terapi itrakonazol dosis denyut dan tampak perbaikan klinis yang signifikan pada lesi. Prognosis pada pasien dubius ad bonam. Pengamatan lanjutan masih perlu dilakukan untuk mengamati kesembuhan secara klinis maupun mikologi, efek samping terapi, dan komplikasi penyakit.